Răspuns :
[tex]a) \frac{4}{3} + \frac{7}{12} = \frac{16}{12} + \frac{7}{12} = \frac{16 + 7}{12} = \frac{23}{12} [/tex]
[tex]b) \frac{8}{14} + \frac{2}{7} = \frac{8}{14} + \frac{4}{14} = \frac{8 + 4}{14} = \frac{12}{14} = \frac{6}{7} [/tex]
[tex]c) \frac{2}{3} + \frac{5}{4} = \frac{8}{12} + \frac{15}{12} = \frac{8 + 15}{12} = \frac{23}{12} [/tex]
[tex]d) \frac{17}{6} - \frac{5}{3} = \frac{17}{6} - \frac{10}{6} = \frac{17 - 10}{6} = \frac{7}{6} [/tex]
[tex]e) \frac{5}{12} - \frac{1}{8} = \frac{10}{24} - \frac{3}{24} = \frac{10 - 3}{24} = \frac{7}{24} [/tex]
[tex]b) \frac{8}{14} + \frac{2}{7} = \frac{8}{14} + \frac{4}{14} = \frac{8 + 4}{14} = \frac{12}{14} = \frac{6}{7} [/tex]
[tex]c) \frac{2}{3} + \frac{5}{4} = \frac{8}{12} + \frac{15}{12} = \frac{8 + 15}{12} = \frac{23}{12} [/tex]
[tex]d) \frac{17}{6} - \frac{5}{3} = \frac{17}{6} - \frac{10}{6} = \frac{17 - 10}{6} = \frac{7}{6} [/tex]
[tex]e) \frac{5}{12} - \frac{1}{8} = \frac{10}{24} - \frac{3}{24} = \frac{10 - 3}{24} = \frac{7}{24} [/tex]